SEMINAR DAMPAK PENGGUNAAN GADGET PADA KESEHATAN ANAK DI SDN REJOSARI: SEMINAR DAMPAK PENGGUNAAN GADGET PADA KESEHATAN ANAK DI SDN REJOSARI - Erick Burhaein; Oknanda Prastiyo; Roidil Zubaidah; Anggun Larasati (CV SWA Anugerah, 2023)
Real Work Lectures (KKN) are a real example of the work carried out by teachers and students in implementing the Tri Dharma of Higher Education, which includes the service aspect. By using democratic knowledge, universities collaborate with the community through community service activities for the Rejosari village community. The aim of this service is to increase local community awareness about the importance of education to assist the government in educating children in this country. Activities carried out include informing students about the impact of using gadgets on their social development and teaching them how to use used goods. The results of the service show an increase in community enthusiasm and understanding, especially teachers and parents